Plasmid profile analysis in identification of epidemic strains of Salmonella enterica serovar Enteritidis - Miljković-Selimović Biljana; Lepšanović Zorica; Babić Tatjana; Kocić Branislava; Ranđelović Gordana (Vojnosanitetski Pregled)
Background/Aim. As illness caused by Sallmonella enterica serovar Enteritidis (S. Enteritidis) occurs not only as sporadic cases but as outbreaks, to reveal the source and routes of spreading of infection it is necessary to identify epidemic strain by the use of some typing methods. To determine whether plasmid profile analysis, as genotyping method, could be applied for the investigation of epidemic strains, isolates of S. Enteritidis, recovered from patient's stools and food associated with outbreaks and those isolated from sporadic cases of diarrhea, were investigated. Methods. Investigation of antibiotic resistance was performed by Kirby - Bauer disc-diffusion method. Isolation of plasmid DNA was carried out by Birnboim and Dolly alkaline lysis method, modified by Ish-Horovitz. Results. Out of 276 izolates of S. Enteritidis 94 were isolated from patient's stools and food associated with outbreaks and 182 were isolated from sporadic cases of diarrhea. The presence of 12 plasmid profiles was established. An average correlation degree of plasmid profiles between the strains was 0.84, that implies high degree of similarity of plasmid profiles of epidemic and non- epidemic strains isolated at our geographic region for the given period of time. Conclusion. The strains of S. Enteritidis, isolated in outbreaks of enterocolitis as well as from spordic cases of diarrhea in the same period of time and at the same area, frequently exhibit the same plasmid profile characterized by a single plasmid of 38 MDa. Therefore, in most cases plasmid profile analysis is not valuable in the identification of epidemic strains of S. Enteritidis. However, for this purpose plasmid profile analysis could be used when drug-resistant strains of S. Enteritidis are isolated, as they often possess additional resistant plasmids what increases discrimination power of this method.